The Role of Visum Et Repertum In Assisting The Direction Of Criminal Charges In Cases Of Assault Resulting In Loss Of Life In The Sleman District Prosecutor's Office - Kurniansyah, Rahmat; Isnawan, Fuadi (JUNCTO: Jurnal Ilmiah Hukum, 2024)
The act of beating is a phenomenon that is difficult to disappear in social life. A written report made by experts or a Visum et Repertum is needed to find the perpetrators and the cause of the beating. Visum et Repertum play a crucial role in influencing the course of criminal prosecution in cases of battering by strengthening existing evidence. However, to increase its effectiveness as valid evidence in law enforcement, various technical and social challenges still need to be overcome. This study aims to determine the role of Visum Et Repertum in influencing the direction of criminal charges in cases of beating that resulted in loss of life at the Sleman District Attorney's Office and to find out the obstacles of law enforcement officials when making Visum Et Repertum as valid evidence in assisting the direction of criminal charges. The research method used is empirical juridical research, using a statutory approach. The data is arranged systematically and then analyzed descriptively and qualitatively. The results showed that the role of Visum Et Repertum in influencing the direction of criminal charges in cases of beating is to strengthen the evidence even though there is already witness testimony and testimony of the defendant. Visum Et Repertum is also able to provide clarity and grounds for the public prosecutor to increase his confidence to make a criminal charge. Meanwhile, the obstacles of law enforcement officials in making the Visum Et Repertum valid evidence are technical obstacles and also obstacles to rejection from the victim's family, where technical obstacles investigators must wait several days or weeks to get the results of the Visum Et Repertum since the victim was delivered.